2009
DOI: 10.1007/s10734-009-9240-y
|View full text |Cite
|
Sign up to set email alerts
|

International education as soft power? The contributions and challenges of Canadian foreign policy to the internationalization of higher education

Abstract: This paper explores the role of the Canadian federal government in two foreign policy areas: overseas development assistance and international cultural relations by providing a brief history of the federal government's engagement in both policy areas and highlighting the contributions and challenges of Canadian foreign policy to the internationalization of Canadian higher education. More broadly, the paper explores the unique characteristics of the Canadian federal government's role in higher education policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 8 publications
1
55
0
10
Order By: Relevance
“…In North America, Melody Viczko and Clara Tascón (2016) found that the Canadian federal government endeavored to own and drive the internationalization of higher education as a diplomatic venture, while the provincial and territorial approach to internationalization was minimized by the federal approach. Accordingly, Roopa Desai Trilokekar (2010) pointed out that there had been a narrowing of vision in Canada, a focus on only short-term objectives and limited dialogue between academics and the government, which challenged the policy development of the internationalization of Canadian higher education. There is a dearth of literature regarding the policymaking that promotes the internationalization of American higher education.…”
Section: Promotion Of the Internationalization Of Higher Educationmentioning
confidence: 99%
“…In North America, Melody Viczko and Clara Tascón (2016) found that the Canadian federal government endeavored to own and drive the internationalization of higher education as a diplomatic venture, while the provincial and territorial approach to internationalization was minimized by the federal approach. Accordingly, Roopa Desai Trilokekar (2010) pointed out that there had been a narrowing of vision in Canada, a focus on only short-term objectives and limited dialogue between academics and the government, which challenged the policy development of the internationalization of Canadian higher education. There is a dearth of literature regarding the policymaking that promotes the internationalization of American higher education.…”
Section: Promotion Of the Internationalization Of Higher Educationmentioning
confidence: 99%
“…It functioned as a "generous funder" that enabled Canadian universities to engage in large scale, long term international projects (Trilokekar, 2010). In addition, the agency also provided additional indirect support to international higher education and research through its funding of other units such as the International Development Research Centre (Trilokekar, 2010).…”
Section: Funding For Internationalizationmentioning
confidence: 99%
“…In addition, a considerable number of studies indicate that higher education plays an important role in promoting and conveying the soft power capacity of countries, which subsequently enhances their overall international and regional influence (for example Nye, 2005;Watanabe and McConnell, 2008;Stetar et al, 2009;Whitney and Shambaugh, 2009;Trilokekar, 2010). This political imperative of higher education illustrates how nations can use higher education as a means to gain strategic political advantage.…”
Section: Education Hub As a Conceptmentioning
confidence: 99%